Motion Optimization and Control of Single and Multiple Autonomous Aerial, Land, and Marine Robots - Ghabcheloo, Reza; Pascoal, Antonio M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on a number of timely and challenging issues in areas that support the design, implementation, and experimental testing of single and multiple autonomous air, land, and marine robots. Special emphasis is placed on the methods and techniques employed for motion planning and control that are rooted in solid theoretical concepts. Applications are also addressed in the area of advanced manipulator control. The reprint affords the reader a well-balanced presentation of a wide spectrum of topics that include, but are not limited to, the generation of optimal collision-free trajectories for heterogeneous vehicles working collaboratively or independently, the rapid adaptation of manipulator trajectories to task perturbations, the automatic collision avoidance for surface vessels, the path following controllers for marine and ground robots, the large-scale swarm counterattack strategies, and the optimal actuator configuration design for over-actuated underwater robots.